C60-based hot-electron magnetic tunnel transistor - Gobbi, M. (2012)
A C 60-based magnetic tunnel transistor is presented. The device is based on the collection of spin-filtered hot-electrons at a metal/C 60 interface, and it allows an accurate measurement of the energy level alignment at such interface. A 89% change in the collected current under the application of a magnetic field demonstrates that these devices can be used as sensitive magnetic field sensors compatible with soft electronics.